EXPERIENCING PICTURE WORD INDUCTIVE MODEL (PWIM) FOR TEACHING RECOUNT: HOW IS IT IMPLEMENTED IN CLASSROOM ACTIVITY? - Wahyu, Artanti Ina; Faiza Hawa; Ajeng Setyorini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate how Picture Word Inductive Model (PWIM) strategy is applied to improve students’ skills in writing recount text. 32 tenth graders were involved during the process of this study. Mixed methods were applied to obtain first, the portrays of PWIM implementation in teaching recount text, and second, how this strategy helped students improve their skills in producing recount text. In getting the data, observations, tests, and qustionnaires were done to students. The results of this study show that there is an improvement in scoring from the pretest and post test. It was 76.18 to 83.06. This indicated that the application of Picture Word Inductive Model (PWIM) aiding students to improve the writing skills of recount texts in class X3 students of SMAN 2 Kendal. The Picture Word Inductive Model (PWIM) strategy was applied in a structured manner during the learning process.